1998
DOI: 10.1097/00005176-199805000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and Turner Syndrome

Abstract: This study suggests that celiac disease can be associated with Turner syndrome and even responsible for a failure of growth hormone therapy. Therefore we propose to perform in Turner syndrome patients antiendomysium antibody determination as a screening followed by intestinal biopsy in positive cases. This would be advisable at least before starting growth hormone treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…The prevalence of celiac disease in patients with Turner's syndrome also appears to be higher than in the general population, with a range of 2%-10% and a pooled estimate of 6.3% (95% CI, 4.57%-8.64%). [212][213][214][215][216] As in Down syndrome, patients with celiac disease with Turner's syndrome are DQ2 positive, but the prevalence of DQ2 in patients with Turner's syndrome may not be higher than in the general population. 216 The prevalence of celiac disease may also be increased in patients with Williams syndrome, although limited data are available.…”
Section: Prevalence Of Celiac Disease In Patients With Other Disordersmentioning
confidence: 99%
“…The prevalence of celiac disease in patients with Turner's syndrome also appears to be higher than in the general population, with a range of 2%-10% and a pooled estimate of 6.3% (95% CI, 4.57%-8.64%). [212][213][214][215][216] As in Down syndrome, patients with celiac disease with Turner's syndrome are DQ2 positive, but the prevalence of DQ2 in patients with Turner's syndrome may not be higher than in the general population. 216 The prevalence of celiac disease may also be increased in patients with Williams syndrome, although limited data are available.…”
Section: Prevalence Of Celiac Disease In Patients With Other Disordersmentioning
confidence: 99%
“…This lends weight to the theory that the cause of IBD may be immune dysfunction. The reports of an increased prevalence of coeliac disease in TS [93]have thus far been unsubstantiated.…”
Section: Clinical Manifestations Of Turner Syndrome In Adultsmentioning
confidence: 99%
“…Furthermore, some studies have reported an increased prevalence of CD among patients with Turner’s syndrome [14, 15], and the management of hypogonadism and delayed puberty may be even more complex in untreated CD Turner’s patients. However, more studies are necessary to evaluate correlations between CD and Turner’s syndrome.…”
Section: Pubertymentioning
confidence: 99%